Analysis of Response Time and Quality of Professional Service Provider Care (PPA) with Patient Satisfaction in Hospital Poly Disease in Kartini Mojokerto - Langit Kresna Janitra; Sandu Siyoto; Rahmania Ambarika (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2021)
To create patient satisfaction, the hospital must create and manage a system to obtain more patients and the ability to retain patients. The process of patient care and care is dynamic and involves many Caregiver Professionals (PPA) and involves various service units. There are many problems regarding the lack of satisfaction from health care workers, one of which is due to the long response time. This study aims to analyze the relationship between response time and service quality of health workers with satisfaction of outpatients at Kartini Hospital, Mojokerto. This study used a quantitative analytic design with a cross sectional approach. The population was all unhospitalited patients who had received services the internal medicine poly at Kartini Hospital, Mojokerto with a total of 156 respondents. The sample used Simple Random Sampling totaling 112 respondents. Independent variables are response time and service quality. The dependent variable is outpatient satisfaction. Data analysis using Ordinal Regression. The time of the study was 18-23 March 2020. Based on the results of the Ordinal Regression Test analysis, it shows that the variable that most influences patient satisfaction is the variable service quality with a p-value of 0.013 <0.05, so H0 is rejected and H1 is accepted, so it can be concluded that there is a significant relationship between the quality of health care workers and satisfaction. On Outpatients at Kartini Hospital, Mojokerto Regency